2008
DOI: 10.1007/s11111-008-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Wild foods and household food security responses to AIDS: evidence from South Africa

Abstract: Wild foods may offer unique benefits to households afflicted by AIDS, providing a nutritious and freely available food source at minimal labour and financial costs. This article presents the results of food security assessments in two rural South African sites. Detailed household dietary recalls from 227 households, combined with qualitative work, explored the association of household AIDS proxies (recent morbidity, mortality and orphan fostering) with household food security and dietary composition. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 38 publications
(46 reference statements)
4
40
0
Order By: Relevance
“…As discussed above, WEP consumption often increases during hungry seasons and times of food crisis, but these results show a more general, year-round association of food-insecure families using WEPs as a coping mechanism. Other studies have found similar relationships, where wild foods are used by chronically food-insecure households on a daily basis to supplement nutrition, increase food volume, and stave off hunger (Harris and Mohammed 2003), especially for vulnerable groups such as AIDS-affected families, widows, and the landless (Campbell 1990, Grivetti and Ogle 2000, Kaschula 2008, Fentahun and Hager 2009, FAO 2011a.…”
Section: Indicators Of Household Vulnerability That Influence Wild Edmentioning
confidence: 77%
“…As discussed above, WEP consumption often increases during hungry seasons and times of food crisis, but these results show a more general, year-round association of food-insecure families using WEPs as a coping mechanism. Other studies have found similar relationships, where wild foods are used by chronically food-insecure households on a daily basis to supplement nutrition, increase food volume, and stave off hunger (Harris and Mohammed 2003), especially for vulnerable groups such as AIDS-affected families, widows, and the landless (Campbell 1990, Grivetti and Ogle 2000, Kaschula 2008, Fentahun and Hager 2009, FAO 2011a.…”
Section: Indicators Of Household Vulnerability That Influence Wild Edmentioning
confidence: 77%
“…7,8 Indira had sufficient resources to adhere because of a disability grant; she also had a supportive family. In contrast, Danisa, although committed to ensuring her health and never having missed a clinic visit, was unable to adhere due to insufficient food.…”
Section: Resolve Weakened By Food Insecuritymentioning
confidence: 99%
“…However, emerging case studies and reviews of the issue parallel insights from earlier work on gender divisions of labor in natural resource management [5,13,29]. Harvesting forest-based foods, especially vitamin-rich foods that supplement household consumption, is often considered "women's work" [4,8,51,76]. Case studies in Africa and elsewhere show that women living near forests in the developing world are often responsible for collecting fuelwood and other subsistence products [77].…”
Section: Forests Food Security and Gendermentioning
confidence: 92%
“…3 Forests may not directly contribute a significant percentage of calories in rural diets, but new evidence suggests that forests may play a role in preventing "hidden hunger"-micronutrient deficiencies that affect billions [47]. Forest foods are a source of valuable micronutrients like iron, vitamin A, vitamin C, folate, calcium and others [4,[48][49][50][51][52]. Consumption of diverse wild plant and animal foods is associated with adequate nutrition in many cases [4,43,[53][54][55][56][57][58][59].…”
Section: Forests Food Security and Gendermentioning
confidence: 99%